The Punishment Gap: School Suspension and Racial Disparities in Achievement. (8th January 2016) - Morris, Edward W.; Perry, Brea L.
Abstract : While scholars have studied the racial "achievement gap" for several decades, the mechanisms that produce this gap remain unclear. In this article, we propose that school discipline is a crucial, but under-examined, factor in achievement differences by race. Using a large hierarchical and longitudinal data set comprised of student and school records, we examine the impact of student suspension rates on racial differences in reading and math achievement. This analysis—the first of its kind—reveals that school suspensions account for approximately one-fifth of black-white differences in school performance. The findings suggest that exclusionary school punishment hinders academic growth and contributes to racial disparities in achievement. We conclude by discussing the implications for racial inequality in education. Mientras que los eruditos han estudiado la "brecha racial educativa" desde hace varias décadas, los mecanismos que producen este vacío no están claros. En este trabajo, proponemos que la disciplina escolar es muy importante, pero poco examinada en el factor en las diferencias de rendimiento según la raza. Utilizando un conjunto de datos de jerárquica y datos longitudinales compuestos por registros escolares de estudiantes, examinamos el impacto de los tipos de suspensión de los estudiantes y las diferencias raciales en la lectura y el rendimiento en matemáticas. Este análisis es primero de su tipo y revela que las suspensiones escolares representan aproximadamente una quinta parte de las diferencias entre el rendimiento escolar entre negros-blancos. Los hallazgos sugieren que el castigo de la escuela de exclusión dificulta el crecimiento académico y contribuye a las disparidades raciales en el rendimiento académico. Concluimos con una discusión de las implicaciones para la desigualdad racial en la educación.